(untitled) (Pravaha, 2024)
This study aimed to examine the gender effect on organizational performance and the moderating impact of gender between HRM practices and organizational performance. 2251 officer-level employees of nine Nepalese public financial institutions were the population. Among them, 430 was the sample size. The purposive sampling method was used to select the sample. An independent sample t-test is applied to compare the organizational performance of males and females. Process Macro Model One is used to examine the moderating impact of gender on the relationship between HRM practices and organizational performance. The result showed that organizational performance is significantly different between male and female. Gender moderated the association between HRM practices and organizational performance in Nepal’s public financial institutions. Gender are crucial factors that improve the connection between HRM practices and organizational performance.